Feminist philosophy quarterly (Western University, 2015)
"Feminist Philosophy Quarterly (FPQ) is an online, open access, peer-reviewed journal dedicated to promoting feminist philosophical scholarship. We welcome submissions from all areas and traditions of feminist philosophy, and our goal is to be a platform for philosophical research that engages the problems of our time in the broader world."--About page, viewed December 3, 2015.